The Effect of Hybrid Learning Method on the Effectiveness of Islamic Religious Education Learning - Ahmad Khumaidi; Kustiana Arisanti (MUMTAZ : Jurnal Pendidikan Agama Islam, 2026)
Hybrid learning is a learning method that combines online and conventional learning. The initial definition of this theory was put forward by Graham, namely the combination of face-to-face learning with computer-based (online) learning. The COVID-19 pandemic that hit the world several years ago has had a significant impact on people's lifestyles, one of which is in the field of education. With the social distancing restrictions implemented by the government, distance learning (online classes) has been echoed, causing culture shock in society. Concerns about the effectiveness of home learning have also been questioned, will it provide a positive contribution to students or will it actually make learning passive and ineffective. This study aims to determine whether there is an effect of hybrid learning on learning effectiveness and how significant that influence is. Therefore, this study uses quantitative methods to obtain precise and accurate results on the relationship between hybrid learning and learning effectiveness. The benefits of this study are to add references on hybrid learning and learning effectiveness and provide input for schools to consider in making policies, especially in Islamic Religious Education (PAI) learning. The results of the questionnaire distributed to students obtained an R value (correlation) of 0.451 and an R square value of 0.203. Therefore, there is a 45.1% correlation between variables X and Y, with variable X influencing variable Y by 20.3%. Therefore, it can be concluded that the hybrid learning method has a positive and significant influence on the effectiveness of Islamic Religious Education learning at Probolinggo 1st State Senior High School (SMAN).